2020
DOI: 10.1371/journal.pone.0228794
|View full text |Cite
|
Sign up to set email alerts
|

TNFα-mediated activation of NF-κB downregulates sodium-iodide symporter expression in thyroid cells

Abstract: The sodium-iodide symporter (NIS) mediates transport of iodide across the basolateral membrane of thyroid cells. NIS expression in thyroid cancer (TC) cells allows the use of radioactive iodine (RAI) as a diagnostic and therapeutic tool, being RAI therapy the systemic treatment of choice for metastatic disease. Still, a significant proportion of patients with advanced TC lose the ability to respond to RAI therapy and no effective alternative therapies are available. Defective NIS expression is the main reason … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Then, the mRNA expression of iNOS was increased and that of Arg-1 was decreased in the PMA group compared with the Sal B group. PMA has been shown to induce canonical NF-κB-dependent transcription by acting through the direct activation of protein-kinase-C 56 , 57 . Moreover, the ELISA results indicated that the TNF-α and IL-6 levels were increased, and the IL-10 level was decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the mRNA expression of iNOS was increased and that of Arg-1 was decreased in the PMA group compared with the Sal B group. PMA has been shown to induce canonical NF-κB-dependent transcription by acting through the direct activation of protein-kinase-C 56 , 57 . Moreover, the ELISA results indicated that the TNF-α and IL-6 levels were increased, and the IL-10 level was decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Higher NIS expression is associated with higher uptake of 131 I by thyroid cell [18], [34]. Thyroid cells that do not respond to radioiodine can be lost NIS expression [15], [17], [23], [24]. The availability of specific polyclonal and monoclonal anti-hNIS antibodies has allowed the investigation of NIS protein expression levels in various thyroid tissues.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some thyroid cancers and metastases showed low uptake of 131 I compare to healthy thyroid tissues [16]. One-third of advanced DTC metastases show low avidity to iodine [8], [17], [18], [19]. Losing the ability to concentrate iodine can occur during the progression of the disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, we added dexamethasone (from day 30) and the TGFb inhibitor SB431542 (from day 37), based on transcriptomic data showing substantial levels of TGFb pathway markers (Extended data Fig. 2f) among NKX2-1 cells, and the known inhibition of thyroid differentiation by inflammation and TGFb pathway stimulation [27][28][29][30][31] .…”
Section: Induction Of Thyroid Statusmentioning
confidence: 99%